2019
DOI: 10.1038/s41598-019-53964-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel ACE inhibitory tripeptides from ovotransferrin using bioinformatics and peptidomics approaches

Abstract: Food-derived ACE inhibitory peptides have recently attracted increased attention. This work focused on a more efficient in silico method to find ACE inhibitory peptides from ovotransferrin. In this work, ovotransferrin was digested into peptides by virtual enzymolysis. Subsequently, in vitro ACE inhibitory activity of potential tripeptides was conducted following the peptide score, toxicity, and water solubility prediction. Both pharmacophore study and flexible docking were applied to analyze ACE inhibition me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Recently, Yu et al, (2019) exhibited potent ACE-inhibitory of ovotransferrin hydrolysates of 19 enzymes and one combination obtained from in silico hydrolysis. In addition, the peptides of ovotransferrin possess various immunomodulatory activities (Liu et al, 2017;Jiao et al, 2019), anti-inflammatory (Wang et al, 2017), and cytotoxic (Yi et al, 2017) activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yu et al, (2019) exhibited potent ACE-inhibitory of ovotransferrin hydrolysates of 19 enzymes and one combination obtained from in silico hydrolysis. In addition, the peptides of ovotransferrin possess various immunomodulatory activities (Liu et al, 2017;Jiao et al, 2019), anti-inflammatory (Wang et al, 2017), and cytotoxic (Yi et al, 2017) activities.…”
Section: Introductionmentioning
confidence: 99%
“… Lee et al (2006) found that one peptide from ovotransferrin with the peptide sequence of Lys-Val-Arg-Glu-Gly-Thr-Thr-Tyr has an ACE-inhibitory activity that can be used as a pro-drug to reduce blood pressure. Recently, Yu et al. (2019) exhibited potent ACE-inhibitory of ovotransferrin hydrolysates of 19 enzymes and one combination obtained from in silico hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Majumder et al ( 2015 ) reported that the ovotransferrin-derived peptide Ile-Arg-Trp increased the ACE-inhibitory activity but decreased the expression of proinflammatory gene in mesenteric arteries of spontaneously hypertensive rats. Recently, Yu et al ( 2019 ) reported that Glu-Trp-Leu obtained from in silico hydrolysis of ovotransferrin using 19 enzymes and one enzyme combination showed potent ACE-inhibitory activity. Moon et al ( 2017 ) reported that the promod 278P hydrolysate of ovotransferrin had 76.82 ± 1.28% ACE-inhibitory activity at 10 mg/mL concentration.…”
Section: Functional Properties Of Ovotransferrin-derived Peptidesmentioning
confidence: 99%
“…ACE-inhibitory activity was measured followed by high-performance liquid chromatography following a method reported previously (Yu et al, 2019).…”
Section: In Vitro Ace-inhibitory Activity Assaymentioning
confidence: 99%